Pressure-temperature phase diagram of the generalized Hubbard model with correlated hopping at half-filling - Didukh, L.; Hankevych, V. (Condensed Matter Physics, 2001)
In the present paper, the pressure-temperature phase diagram of a generalized
Hubbard model with correlated hopping in a paramagnetic state
at half-filling is determined by means of a generalized mean-field approximation
in the Green function technique. The constructed phase diagram
describes the metal-to-insulator transition with increasing temperature, and
the insulator-to-metal transition under the action of external pressure. The
phase diagram can explain the paramagnetic region of the phase diagrams
of some transition metal compounds Робота присвячена побудові фазової діаграми тиск-температура
узагальненої моделі Габбарда з корельованим переносом у парамагнітному стані при половинному заповненні зони з використанням
узагальненого наближення Гартрі-Фока в методі функцій Ґріна. Побудована фазова діаграма описує перехід з металічного стану в діелектричний при збільшенні температури і перехід з діелектричного
стану в металічний під дією зовнішнього тиску. Фазова діаграма може пояснити парамагнітні області фазових діаграм деяких сполук перехідних металів.